Programming Morphogenesis through Systems and Synthetic Biology. Issue 4 (April 2018) - Velazquez, Jeremy J.; Su, Emily; Cahan, Patrick; Ebrahimkhani, Mo R.
Abstract : Mammalian tissue development is an intricate, spatiotemporal process of self-organization that emerges from gene regulatory networks of differentiating stem cells. A major goal in stem cell biology is to gain a sufficient understanding of gene regulatory networks and cell–cell interactions to enable the reliable and robust engineering of morphogenesis. Here, we review advances in synthetic biology, single cell genomics, and multiscale modeling, which, when synthesized, provide a framework to achieve the ambitious goal of programming morphogenesis in complex tissues and organoids. Highlights: Stem cell-derived multicellular systems and organoids have opened new opportunities to emulate and understand human development in vitro and provide novel patient specific tissue surrogates for disease modeling. Single cell sequencing technologies and spatial tissue analysis provide a wealth of information on cellular fate and function and offer invaluable opportunities to decipher developmental processes. Mammalian synthetic biology utilizes designer synthetic gene circuits to program cell fate and functions towards a desired outcome. Engineering morphogenesis is an emerging area of science that integrates engineering principles with developmental biology to control and guide collective cell behaviors.